SISTEM NILAI DAN SIKAP MASYARAKAT TERHADAP KONSERVASI S. belangeran DARI HUTAN KERANGAS - Kissinger Kissinger; Ahmad Yamani; Rina Muhayah Noor Pitri (EnviroScienteae, 2016)
Shorea belangeran is one type of tree in heath forest. IUCN red list classifying S. belangeran in the critically endangered. The aim of this study are 1) to analyze the public attitudes towards conservation of S. belangeran, 2) to determine management chosen for S. belangeran in heath forest 3) to develop an implementation strategy of conservation for S. belangeran in  heath forest as material sources of natural medicine. Data collecting of public attitudes conducted by semi-structured interviews on local communities in the field. Identifying the attitude of society through 1) characterizing the value system of the community toward S. belangeran. 2) Disclosure of S. belangeran from kerangas forest. There is four value system toward S. belangeran from heath forest, namely the economic, socio-cultural values, socio-cultural values and religious values. Ethnobotany knowledge of community about the use of S. belangeran is a traditional ecological knowledge. S. belangeran is not only seen in the knowledge of their medicinal properties but more complex includes a trust or confidence. Unfortunately, the system of values in society are not properly transferred to the next generation. The attitude of the community to actively participate in the S. belangeran are weak. The weakness of community attitudes toward S. belangeran and the rupture of value systems of S. belangeran are the issues of conservation that must be resolved.